RGO / Zr-MOF composite sensing material for noise, preparation method of rGO / Zr-MOF composite sensing material and application of rGO / Zr-MOF composite sensing material in noise sensor
By using a two-dimensional thin film noise sensor prepared by using rGO/Zr-MOF composite sensing material, the problem of noise sensors being susceptible to interference in complex environments in the prior art is solved, and higher sensitivity and stability are achieved, and it can effectively capture it. and convert noise signals.
Patent Information
- Application Number
- CN202411516174.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
Existing noise sensors are susceptible to interference from electromagnetic noise, mechanical vibration and other in complex environments, resulting in distortion of detection signals and affecting the accuracy of detection results.
The rGO/Zr-MOF composite sensing material was prepared by chemical reduction and self-assembly technology, combined with copper foil substrate and liquid precipitation method, a noise sensor with a two-dimensional film structure was prepared.
It improves the sensitivity and stability of the sensor, enhances the ability to capture and convert noise signals, covers a wider noise frequency range, and ensures consistent performance in long-term use.
Smart Images

Figure CN119390995A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new sensing materials, and in particular to an rGO / Zr-MOF composite sensing material for noise, a preparation method thereof, and application of the composite sensing material in a noise sensor. Background Art
[0002] During the operation of power equipment such as transformers, noise signals of different frequencies and intensities will be generated due to mechanical structure, electromagnetic field changes and the operation of the cooling system. These signals contain important information about the equipment's operating status, such as load changes, temperature fluctuations, vibration characteristics, etc. By real-time monitoring and analysis of these noise signals, potential problems with the equipment can be discovered in a timely manner, failures can be prevented, and the stable operation of the power system can be ensured.
[0003] Although traditional electrical microphones can detect these noise signals, this type of detection instrument has always had shortcomings such as susceptibility to electrical interference, poor electrical insulation performance, and low detection sensitivity. Electrical sensor technology has developed rapidly in recent years. Its high precision, high sensitivity, and high reliability make the detection of noise signals more accurate and reliable. The application of micro-nano processing technology makes sensor elements smaller and more sensitive, and can capture weaker noise signals. However, current noise sensors still have some shortcomings. For example, they may be subject to various interferences in complex environments, such as electromagnetic noise, mechanical vibration, etc. These interferences may cause distortion of the detection signal and affect the accuracy of the detection results. Summary of the invention
[0004] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a rGO / Zr-MOF composite sensing material for noise, a preparation method thereof, and an application thereof in a noise sensor.
[0005] A method for preparing a noise rGO / Zr-MOF composite sensing material of the present invention comprises the following steps: S1. Ultrasonic dispersion of graphene oxide GO in ethanol, then adding hydroiodic acid, performing oil bath reaction, then removing iodine and centrifuging to obtain a solid product, centrifugally washing and drying the solid product to obtain rGO; S2, dissolving the zirconium salt in N,N-dimethylformamide, then adding the organic ligand 4,4'-stilbene dicarboxylic acid thereto with stirring, then adding the rGO prepared in S1 and performing ultrasonic dispersion, and then performing an oil bath reaction; S3. The reaction solution obtained in S2 is centrifuged and washed to remove the supernatant, thereby obtaining a rGO / Zr-MOF composite sensing material for noise.
[0006] Furthermore, in step S1, the mass volume ratio of graphene oxide GO to hydroiodic acid is 5-10 mg: 1-3 ml.
[0007] Furthermore, in step S1, the oil bath reaction is carried out at 100-150° C. for 1-3 hours.
[0008] Furthermore, in step S1, iodine is removed by adding sodium bisulfite and water to the oil bath reaction solution, standing for 3 days to remove salt and then centrifuging to obtain a solid product; washing with ethanol and water three times by centrifugation respectively, and drying at 60°C for a period of time to obtain rGO.
[0009] Furthermore, the zirconium salt is ZrCl4, and the mass ratio of the zirconium salt, 4,4'-stilbene dicarboxylic acid and rGO is 0.1~0.3:0.1~0.3:0.05~0.2.
[0010] Furthermore, in step S2, the oil bath reaction is carried out at 100-150° C. for 12-24 h, so that the metal Zr ions and the organic ligands self-assemble into a porous material loaded on the surface of rGO.
[0011] Furthermore, the specific operation of step S3 is to transfer the reaction solution to a centrifuge tube, remove the supernatant by centrifugation, add N,N-dimethylformamide and ethanol, centrifuge and wash three times, and then remove the supernatant to obtain a gray-black solid rGO / Zr-MOF.
[0012] The noise rGO / Zr-MOF composite sensing material was prepared by the above-mentioned preparation method.
[0013] A method for preparing a two-dimensional thin film device, comprising dispersing the above-mentioned rGO / Zr-MOF composite sensing material in deionized water, then dropping it on a substrate, and letting it stand to obtain a rGO / Zr-MOF graphene-based two-dimensional thin film device; the volume ratio of the rGO / Zr-MOF composite sensing material to deionized water is 5~10g:100~500mL.
[0014] The two-dimensional thin film device as described above is used to prepare a noise sensor.
[0015] The rGO / Zr-MOF composite sensing material prepared by the present invention can efficiently receive sound waves and convert them into measurable electrical signals as a sensing element. rGO has high electrical conductivity, high specific surface area and good mechanical properties, which make it an ideal conductive and sensing material in noise sensors. In the application of noise sensors, rGO can efficiently transmit electrical signals and respond sensitively to small deformations caused by noise. Zr-MOF, as a porous material, has a high specific surface area, excellent adsorption properties and structural stability. The combination of the two not only enhances the electrical conductivity and mechanical stability of the material, but also expands the specific surface area, which is conducive to the capture and conversion of noise signals, thereby improving the sensitivity of the sensor, allowing the sensor to cover a wider noise frequency range and meet the needs of different application scenarios.
[0016] The rGO / Zr-MOF composite sensing material prepared by chemical reduction and self-assembly technology in the present invention has a stable structure and is not easily affected by the external environment. This stability ensures the performance consistency of the sensor during long-term use and improves its durability and reliability.
[0017] The present invention uses copper foil as a substrate, and evenly deposits rGO / Zr-MOF composite sensing materials on copper foil by liquid precipitation method to prepare a noise sensor with a two-dimensional thin film structure. The noise effect causes the film to deform or vibrate, resulting in changes in the distance and contact state between rGO sheets. This change changes the transmission path of electrons between rGO sheets, thereby affecting the resistance value of the material, and its resistance value will change. This change is proportional to the magnitude of the pressure, so the characteristics of the noise can be inferred by measuring the change in resistance value. The presence of Zr-MOF may play a certain supporting and stabilizing role on the rGO sheets through its skeleton structure, making the deformation more uniform and controllable.
[0018] The degree of reduction of rGO directly affects its conductivity and mechanical properties; during the preparation process, the degree of reduction of rGO can be optimized by controlling conditions such as the amount of hydroiodic acid and the reaction time, thereby improving the performance of the sensor.
[0019] The present invention self-assembles rGO with ZrCl4 and 4,4'-stilbene dicarboxylic acid in N,N-dimethylformamide, limits key steps such as the ratio of reactants, reaction temperature, time and ultrasonic treatment, ensures the uniformity and performance stability of the composite material, and by optimizing these conditions, achieves a close combination and synergistic effect between rGO and Zr-MOF, thereby improving the sensitivity and stability of the sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM image of the rGO / Zr-MOF composite sensing material prepared in Example 1; Figure 2 This is the XRD pattern of the rGO / Zr-MOF composite sensing material prepared in Example 1; Figure 3 This is a SEM image of the two-dimensional thin film device prepared in Example 4; Figure 4 The output voltage signal of the two-dimensional thin film device prepared in Example 4; Figure 5 These are the sensitivity test results of the two-dimensional thin device prepared in Example 4. DETAILED DESCRIPTION
[0021] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0022] Example 1 1. Preparation of reduced graphene oxide rGO 5 mg of graphene oxide GO was placed in a flask containing 10 mL of ethanol. After ultrasonic cleaning for 10 min, 1 ml of hydroiodic acid was added, the flask was sealed, transferred to an oil bath, and heated to 100 ° C for 1 h. 2 g of sodium bisulfite and 50 mL of water were added to remove iodine, and the product was allowed to stand for 3 days to remove salt and then centrifuged to obtain a solid product. The solid product was washed three times with ethanol and water respectively, and dried in a drying oven at 60 ° C for 24 h to obtain the desired rGO product.
[0023] 2. Preparation of rGO / Zr-MOF Add 10 mL of organic solvent N,N-dimethylformamide into a flask, weigh 0.1 g of ZrCl4 metal salt and add it, stir at room temperature for 10 min, add 0.1 g of 4,4'-stilbene dicarboxylic acid as an organic ligand after it is completely dissolved, continue stirring for 10 min, add 5 mg of the above-prepared rGO, ultrasonicate in an ultrasonic cleaner for 1 h to fully disperse the rGO, transfer it to an oil bath, heat to 100 ° C to react for 12 h, so that the metal Zr ions and organic ligands self-assemble into porous materials loaded on the rGO surface.
[0024] The reaction solution was transferred to a centrifuge tube, centrifuged at 14000 rpm, and the supernatant was removed. N,N-dimethylformamide and ethanol were added and centrifuged at 14000 rpm for three times, and then the supernatant was removed to obtain a gray-black solid rGO / Zr-MOF.
[0025] Example 2 1. Preparation of reduced graphene oxide rGO 7 mg of graphene oxide GO was placed in a flask containing 15 mL of ethanol. After ultrasonic cleaning for 15 minutes, 2 ml of hydroiodic acid was added, the flask was sealed, transferred to an oil bath, and heated to 130 ° C for 2 hours. 3 g of sodium bisulfite and 75 mL of water were added to remove iodine, and the product was allowed to stand for 3 days to remove salt and then centrifuged to obtain a solid product. The solid product was washed three times with ethanol and water respectively, and dried in a drying oven at 60 ° C for 24 hours to obtain the desired rGO product.
[0026] 2. Preparation of rGO / Zr-MOF Add 20 mL of organic solvent N,N-dimethylformamide into a flask, weigh 0.2 g of ZrCl4 metal salt and add it, stir at room temperature for 15 min, add 0.2 g of 4,4'-stilbene dicarboxylic acid as an organic ligand after it is completely dissolved, continue stirring for 15 min, add 7 mg of the above-prepared rGO, ultrasonicate in an ultrasonic cleaner for 2 h to fully disperse the rGO, transfer it to an oil bath, heat to 100~150℃ and react for 20 h, so that the metal Zr ions and organic ligands self-assemble into porous materials loaded on the rGO surface.
[0027] The reaction solution was transferred to a centrifuge tube, centrifuged at 14000 rpm, and the supernatant was removed. N,N-dimethylformamide and ethanol were added and centrifuged at 14000 rpm for three times, and then the supernatant was removed to obtain a gray-black solid rGO / Zr-MOF.
[0028] Example 3 1. Preparation of reduced graphene oxide rGO 10 mg of graphene oxide GO was placed in a flask containing 20 mL of ethanol. After ultrasonic cleaning for 20 min, 3 ml of hydroiodic acid was added, the flask was sealed, transferred to an oil bath, and heated to 150 ° C for 3 h. 4 g of sodium bisulfite and 100 mL of water were added to remove iodine, and the product was allowed to stand for 3 days to remove salt and then centrifuged to obtain a solid product. The solid product was washed three times with ethanol and water respectively, and dried in a drying oven at 60 ° C for 24 h to obtain the desired rGO product.
[0029] 2. Preparation of rGO / Zr-MOF Add 30 mL of organic solvent N,N-dimethylformamide into a flask, weigh 0.3 g of ZrCl4 metal salt and add it, stir at room temperature for 20 min, add 0.3 g of 4,4'-stilbene dicarboxylic acid as an organic ligand after it is completely dissolved, continue stirring for 20 min, add 10 mg of the above-prepared rGO, ultrasonicate in an ultrasonic cleaner for 3 h to fully disperse the rGO, transfer it to an oil bath, heat to 150 ° C to react for 24 h, so that the metal Zr ions and organic ligands self-assemble into porous materials loaded on the rGO surface.
[0030] The reaction solution was transferred to a centrifuge tube, centrifuged at 14000 rpm, and the supernatant was removed. N,N-dimethylformamide and ethanol were added and centrifuged at 14000 rpm for three times, and then the supernatant was removed to obtain a gray-black solid rGO / Zr-MOF.
[0031] Comparative Example 1 Preparation of reduced graphene oxide rGO 5 mg of graphene oxide GO was placed in a flask containing 10 mL of ethanol. After ultrasonic cleaning for 10 min, 1 ml of hydroiodic acid was added, the flask was sealed, transferred to an oil bath, and heated to 100 ° C for 1 h. 2 g of sodium bisulfite and 50 mL of water were added to remove iodine, and the product was allowed to stand for 3 days to remove salt and then centrifuged to obtain a solid product. The solid product was washed three times with ethanol and water respectively, and dried in a drying oven at 60 ° C for 24 h to obtain the desired rGO product.
[0032] Fabrication of two-dimensional thin film devices The two-dimensional thin film device uses 99.9% pure copper foil as the substrate and is prepared by liquid precipitation method. The specific method is as follows: weigh 5~10mg rGO / Zr-MOF powder, add it to 100~500ml deionized water, ultrasonicate it in an ultrasonic cleaner for 1~2h to evenly disperse the rGO / Zr-MOF, and let it stand for 24h to obtain the rGO / Zr-MOF dispersion.
[0033] Use a dropper to take 0.5~2 mL of rGO / Zr-MOF dispersion, then drop it on the copper foil and let it stand for more than 24 hours to obtain a two-dimensional thin film device with rGO / Zr-MOF graphene-based.
[0034] Example 4 Fabrication of two-dimensional thin film devices 99.9% pure copper foil was used as the substrate, and the two-dimensional thin film device was prepared by liquid precipitation method. The specific method is as follows: 5 mg of rGO / Zr-MOF powder was weighed and added to 100 ml of deionized water, and ultrasonicated in an ultrasonic cleaner for 1 hour to evenly disperse the rGO / Zr-MOF, and then the rGO / Zr-MOF dispersion was obtained after standing for 24 hours.
[0035] Use a dropper to take 2 mL of rGO / Zr-MOF dispersion, then drop it on the copper foil and let it stand for more than 24 hours to obtain a two-dimensional thin film device with rGO / Zr-MOF graphene-based.
[0036] The rGO / Zr-MOF powders here are prepared according to Examples 1-3, respectively, and are denoted as two-dimensional thin film device 1#, two-dimensional thin film device 2#, and two-dimensional thin film device 3#, respectively.
[0037] Comparative Example 2 A 2D thin film device was prepared by liquid precipitation method using 99.9% pure copper foil as substrate. The specific method is as follows: 5 mg of rGO powder prepared in Comparative Example 1 was weighed and added to 100 ml of deionized water, and then ultrasonicated in an ultrasonic cleaner for 1 h to uniformly disperse the rGO, and then allowed to stand for 24 h to obtain rGO / Zr-MOF dispersion.
[0038] Use a dropper to take 2 mL of rGO dispersion, then drop it on the copper foil and let it stand for more than 24 hours to obtain a two-dimensional thin film device with rGO graphene base, which is recorded as two-dimensional thin film device 4#.
[0039] Figure 1 This is the SEM image of the rGO / Zr-MOF composite sensing material prepared in Example 1; Figure 1 As shown, the rGO / Zr-MOF composite sensing material prepared in Example 1 is a two-dimensional material with the structural characteristics of reduced graphene oxide (rGO) as a two-dimensional material and excellent conductivity, which enables it to quickly respond and efficiently transmit noise signals into electrical signals in sensor applications. Secondly, the addition of Zr-MOF (zirconium-based metal-organic framework) not only enriches the structural diversity of the composite material, but also enhances the material's ability to identify and capture specific noise frequencies through its surface functionalization characteristics.
[0040] Figure 2 The XRD pattern of the rGO / Zr-MOF composite sensing material prepared in Example 1; Figure 2 As shown, the diffraction peaks of the sensing material rGO / Zr-MOF have the formation of a variety of hybrid products, and the material exists in graphene oxide phase and Zr-MOF phase.
[0041] Figure 3 The SEM image of the two-dimensional thin film device 3# prepared by using the rGO / Zr-MOF composite sensing material prepared in Example 3; Figure 3 It can be seen that the two-dimensional thin film device prepared by the present invention is a piece-by-piece stacking structure, and a precise structure is formed by stacking layers, so that the overall structure of the sensor is compact, light, and flexible, which is easy to carry and install, and is suitable for various portable or embedded devices.
[0042] Figure 4 The output voltage signal of the two-dimensional thin film device 3# prepared by using the rGO / Zr-MOF composite sensing material prepared in Example 3 is a response waveform, which reflects the sensitivity and response performance to the noise signal. Figure 4 It can be seen that the two-dimensional thin film device prepared by the present invention has excellent electrochemical signals, and has high sensitivity and fast response speed to noise signals.
[0043] The sensitivity test of two-dimensional thin film devices 1#-4# was carried out, and the results are as follows Figure 5 As shown in Table 1, Figure 5 The sensitivity test results of the two-dimensional thin film device 3# prepared by using the rGO / Zr-MOF composite sensor material prepared in Example 3. It can be seen that when the test frequency is in the range of 1-20kHz, the average minimum detectable noise sound pressure sensitivity of the two-dimensional thin film device of the present invention is 19.8 μPa / Hz-2 / 1 , with high sensitivity response capability, can be used to detect noise sound waves.
[0044] Table 1 Sensitivity test results of two-dimensional thin film devices 1#-4#
[0045] For matters not mentioned above, the prior art applies.
[0046] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a rGO / Zr-MOF composite sensor material for noise, characterized in that: The steps include: S1. Ultrasonic dispersion of graphene oxide GO in ethanol, then adding hydroiodic acid, performing oil bath reaction, then removing iodine and centrifuging to obtain a solid product, centrifugally washing and drying the solid product to obtain rGO; S2, dissolving the zirconium salt in N,N-dimethylformamide, then adding the organic ligand 4,4'-stilbene dicarboxylic acid thereto with stirring, then adding the rGO prepared in S1 and performing ultrasonic dispersion, and then performing an oil bath reaction; S3. The reaction solution obtained in S2 is centrifuged and washed to remove the supernatant, thereby obtaining a rGO / Zr-MOF composite sensing material for noise.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass volume ratio of graphene oxide GO to hydroiodic acid is 5-10 mg: 1-3 ml.
3. The preparation method according to claim 1, characterized in that: In step S1, the oil bath reaction is carried out at 100-150° C. for 1-3 hours.
4. The preparation method according to claim 1, characterized in that: In step S1, iodine is removed by adding sodium bisulfite and water to the oil bath reaction solution, standing for 3 days to remove salt and then centrifuging to obtain a solid product; washing with ethanol and water three times by centrifugation respectively, and drying at 60° C. for a period of time to obtain rGO.
5. The preparation method according to claim 1, characterized in that: The zirconium salt is ZrCl4, and the mass ratio of the zirconium salt, 4,4'-stilbene dicarboxylic acid and rGO is 0.1~0.3:0.1~0.3:0.05~0.
2.
6. The preparation method according to claim 1, characterized in that: In step S2, the oil bath reaction is carried out at 100-150° C. for 12-24 h, so that the metal Zr ions and the organic ligands self-assemble into a porous material loaded on the surface of rGO.
7. The preparation method according to claim 1, characterized in that: The specific operation of step S3 is to transfer the reaction solution to a centrifuge tube, remove the supernatant by centrifugation, add N,N-dimethylformamide and ethanol, centrifuge and wash three times, and then remove the supernatant to obtain gray-black solid rGO / Zr-MOF.
8. The rGO / Zr-MOF composite sensing material for noise prepared by the preparation method according to any one of claims 1 to 7.
9. A method for preparing a two-dimensional thin film device, characterized in that: The rGO / Zr-MOF composite sensing material as claimed in claim 8 is dispersed in deionized water, then dropped on a substrate and allowed to stand to obtain a rGO / Zr-MOF graphene-based two-dimensional thin film device; the volume ratio of the rGO / Zr-MOF composite sensing material to deionized water is 5~10g:100~500mL.
10. The two-dimensional thin film device according to claim 9 is used to prepare a noise sensor.